THE EFFICIENCY OF PASSENGER TRANSPORTATION IN SUBURBAN - Dronova, T. I. (Science and Transport Progress, 2007)
For the increase of efficiency of prymyskyy passenger transportations the improvement of calculations is offered for transportations and measures on the costs cutting of operations.